AN ANALYSIS ON NON-SPECIALIST OUTPATIENT REFERRALS AT BEJI AND DEPOK JAYA HEALTH CENTERS IN 2018 - Pertiwi, Tasya Caesarena; Basabih, Masyitoh (Journal of Indonesian Health Policy and Administration, 2018)
The Health Social Security Agency (BPJS kesehatan) is one of the government’s efforts to provide quality healthcare for the people. To guarantee its quality and maintain efficiency, a tiered referral system is used. However, there were many problems in its implementation. One of the ways to investigate is to evaluate the non-specialist outpatient referrals (RRNS). Therefore, in March-July 2018, this research was performed in order to analyze whether the system was implemented at Beji and Depok Jaya Health Center. The method used was the qualitative research method, with primary data from in-depth interviews and secondary data from documents. It was discovered that both Centers had optimal RRNS ratios (0%). This was because the doctors at both Centers has provided referrals as indicated and there was feedback on the RRNS total. The civil servant (PNS) doctors at both centers were experienced and skillful, but the number of doctors was insufficient compared to their workload. The non-PNS doctors also were not sufficiently trained. Other problems include insufficient equipment and medication provision.